Environment injustice and public health - Njoku, Anuli U.; Sampson, Natalie R. (Handbook of Social Sciences and Global Public Health, 2023)
Globally, air pollution accounts for approximately one in eight deaths, and diarrheal diseases account for one in nine child deaths annually. Lead exposure contributes to concerns of heart disease, stroke, and developmental intellectual disability. Further, across the world, nearly 23 million people are displaced by extreme weather events each year, which have been exacerbated by climate change and contribute to physical and mental health implications for entire communities. These and many other environmentally related experiences and their subsequent health outcomes are not experienced equally by race, ethnicity, or income, with Black, Brown, and Indigenous communities and low-income communities repeatedly experiencing the heaviest of burdens. Due to a variety of historic and contemporary policy and planning decisions, these patterns of environmental injustice persist on local, national, and global scales. In response, environmental justice (EJ) is a social movement, as well as a belief that people of all backgrounds deserve access to clean air and water and a healthy community in which to thrive. This chapter heavily focuses on the USA and its environmental health inequities, policies, and historic EJ movement. However, in our globalized society, EJ is a global issue that must be addressed as such by the field of public health.
Keywords: Cumulative impacts; Environmental justice; Health equity; Social determinants of health; Systemic racism; dept.pch